Amplification of Language Learning Intelligence through Technology: An Overview - et. al., Mr. V.Mainar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Human life relies on the inventions of different technology. Be it a learner or teacher, both are the users of technology. The modern era or new normal days after Covid-19 has come to different dimension in doing things easier way by using these technology or Artificial Intelligence (AI). Technology converts the human effort into easier and powerful within the short time. After the pandemic, teachers are also in a position to change their style of using traditional teaching to modern pedagogy. The modern pedagogy forces the teachers to use AI more especially in language learning class than using traditional teaching. The paradigm shift in the field of teaching has brought million changes where the teachers became the felicitators and the learners will be testing their knowledge on their own without the help of the teachers in learning new languages. This paper deals with the obstacles faced by the language teachers in using technology, the innovative tools used in aggrandizing the learners ability by using AI in language classroomand how the country like India look at the advancement of technology in a classroom teaching.